ANALISA PEMERIKSAAN INSPEKSI VISUAL ASAM ASETAT PADA WANITA USIA SUBUR DI PUSKESMAS KARAWANG KOTA - Herry Sugiri; A. Achmad Fariji (HSG (Health Science Growth) Journal, 2020)
Cervical cancer cases in Karawang Regency tend to increase every year. For that it is very necessary to do an IVA examination to detect cervical cancer as early as possible. The achievement of the IVA inspection program in Karawang Regency in 2014 is still far below the target, which is only 28%. For that research is necessary. The research design used in this study was an analytical method, with a cross sectional approach. It is hoped that the result of this study can provide additional knowledge for the public to detect early cervical cancer. The result showed that there was a significant relationship between knowledge and IVA examination (p value = 0.000 OR 9.028 95 % CI = 3.27 – 24.88) and there was a significant relationship between attitude and IVA examination (p value = 0.010 , OR 3,4 95 % CI = 1.40 – 8.23) Discussion : Suggestion it is hoped that other researchers will conduct further research using qualitative methods to dig deeper into the determinants of the low IVA examination achievement. To increase the provision of health promoting regarding IVA examinations. Educational institusions participate in improving the IVA examination program through community service activities by carrying out health promotions regarding IVA examinations to the public Keywords : Attitude, IVA, examination, knowledge